Formulasi Sediaan Krim Pelembab Ekstrak Air Buah Semangka (Citrullus lanatus) - Ekayanti, Ni Luh Putu Serly; Darsono, Farida Lanawati; Wijaya, Sumi (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2019)
Watermelon is a tropical fruit which rich of carbohydrates such as sucrose, glucose and fructose that can moisturized the skin. Carotenoids such as lycopene in watermelons can acts as an antioxidant which protected skin from free radicals. Moisturizer are preparations used to improve dry skin. These preparations may decrease the Trans Epidermal Water Loss (TEWL) by forming a thin layer of fat on the surface of the skin as a barrier and restore skin softness. Watermelon extracts in this study are formulated into moisturizing cream. This study aims to determine the effect of the increasing concentration of the watermelon extract against its physical quality, effectiveness, safety, acceptability and cream stability. The watermelon extract obtained using is fresh fruit juice thickened with waterbath thermostat temperature ≤ 800C. Watermelon extract concentration used was 10% (Formula 1), 20% (Formula 2) and 30% (Formula 30. Evaluation of the cream includes the physical quality test; effectiveness test which; safety test; acceptability test and stability test. The results of this study showed the increasing concentrations of watermelon extract affect the results of the evaluation of moisturizing cream were organoleptic, pH, viscosity, dispersive power, adhesion, water washing power, effectiveness, and aseptability. Preparations which have the best quality are formula 3 containing extract 30%.